Forecasting Crime Situation through the Safe Points System for the Development of Public Safety Zones in the Digital Era - thanyasiri, phongthon (Journal of Thai Ombudsman, 2026)
This academic article aims to examine the application of the Safe Points system in forecasting crime situations in order to create safe areas for the public in the digital era under the Office of Justice Affairs, Ministry of Justice. The formulation of policies and strategies in the justice process to ensure public safety requires empirical data that is accurate, comprehensive, and up-to-date in order to effectively support policy decision-making among relevant agencies under the National Justice Administration Development Committee. This study employed documentary research through the review of relevant literature, research studies, and laws. The findings indicate that current crime situations and the delivery of justice to the public have become increasingly complex and rapidly changing in response to social, economic, and technological contexts. Therefore, the development of database systems and big data analytics has become an essential mechanism for supporting modern justice administration in terms of crime prevention, reducing inequality in access to justice, and strengthening public confidence. As the secretariat of the National Justice Administration Development Committee, the Office of Justice Affairs plays a significant role in planning justice policies and strategies. It has continuously collected crime and justice statistics from relevant agencies and produced the White Paper on Crime and Justice to reflect the overall situation and key trends of the country. The study further found that the Office of Justice Affairs has established the National Justice Administration Database Center (NJADC), which represents a newly developed analytical system designed to connect and integrate databases among agencies within the justice process. This initiative is consistent with the government’s digital policy emphasizing data-driven public administration, as well as the 20-Year National Strategy on Security, which focuses on enhancing the safety of people’s lives and property. It also supports the creation of safe spaces for the public under a “People-Centered Approach,” enabling the government to better respond to public needs and enhance safety. To improve the completeness of the database for analytical purposes, the study recommends further integration with other public and private sector databases, as well as the expansion of cooperation at the international level.